Polycystic ovary syndrome: clinical and hormonal - Gutiérrez, Ítalo (2015)
Objective: To evaluate clinical and hormonal findings related to polycystic ovary. Design: Retrospective study. Setting: Gynecology and Infertility Service, Arzobispo Loayza Hospital. Material and Methods: Hormonal profile was determined in 69 reproductive age patients with transvaginal ultrasound diagnosis of polycystic ovaries. Results: Patients presented oligoamenorrhea in 67,7%, infertility in 28,8%, hirsutism in 23,7% and body mass index > 25 in 42,4%. LH was elevated in 47,1 %, LH/FSH > 2 in 24,5% and high testosterone in 20,9 %. Sixty-four per cent of obese women presented oligoamenorrhea, 42,8% hirsutism, 50% infertility and 50% high LH. Conclusion: There was hormonal and clinical correlation with obesity in polycystic ovaries patients.